Message from the Chief Editor Vol.1(1) (Journal of Brain and Spine Foundation Nepal, 2020)
Brain and Spine Foundation Nepal is a not-for profit organization registered (Registration No. 226156/076/077) on 13th Ashwin 2076. The Foundation aims to work with all those involved in prevention, diagnosis and treatment of brain and spine disorders and diseases. One of the guiding principle of the foundation is dissemination of medical information related to these diseases.In Nepal, there are two neurosurgical journals being regularly published Nepal Journal of Neuroscience (NJNS, ISSN 1813-1948), official journal of Nepalese Society of Neurosurgeons (NESON) and Eastern Green Neurosurgery (EGN, ISSN 2705-4470), published by Department of Neurosurgery, B and C Medical College and Teaching Hospital, Birtamode. NJNS is being published since January 2004 and EGN is being published since April 2019. However these journals accept articles mainly from neurologists and neurosurgeons.The objective of any journal is to provide information about various research projects, interaction with own fraternity and to publish scientific articles of research and clinical practice. We at the Foundation believe that the neurological problems should be tackled with multidimensional probe. We focus on awareness programs, information dissemination and involve other healthcare workers like physiotherapists, physiatrists, neuro nurses, emergency physicians, neuro-anaesthesiologists, pain physicians etc. We aim to publish this journal twice a year, on March and on September.We request all healthcare workers who take care of brain and spine patients to send articles related to their work. You can send case reports, review articles and original articles for publication in this journal.